Effects of nicotine on response inhibition and interference control. - Ettinger, Ulrich; Faiola, Eliana; Kasparbauer, Anna-Maria; Petrovsky, Nadine; Chan, Raymond; Liepelt, Roman; Kumari, Veena (Psychopharmacology, 2017)
Nicotine is a cholinergic agonist with known pro-cognitive effects in the domains of alerting and orienting attention. However, its effects on attentional top-down functions such as response inhibition and interference control are less well characterised. Here, we investigated the effects of 7 mg transdermal nicotine on performance on a battery of response inhibition and interference control tasks. A sample of N = 44 healthy adult non-smokers performed antisaccade, stop signal, Stroop, go/no-go, flanker, shape matching and Simon tasks, as well as the attentional network test (ANT) and a continuous performance task (CPT). Nicotine was administered in a within-subjects, double-blind, placebo-controlled design, with order of drug administration counterbalanced. Relative to placebo, nicotine led to significantly shorter reaction times on a prosaccade task and on CPT hits but did not significantly improve inhibitory or interference control performance on any task. Instead, nicotine had a negative influence in increasing the interference effect on the Simon task. Nicotine did not alter inter-individual associations between reaction times on congruent trials and error rates on incongruent trials on any task. Finally, there were effects involving order of drug administration, suggesting practice effects but also beneficial nicotine effects when the compound was administered first. Overall, our findings support previous studies showing positive effects of nicotine on basic attentional functions but do not provide direct evidence for an improvement of top-down cognitive control through acute administration of nicotine at this dose in healthy non-smokers.